Conceptual Art - Godfrey, Tony (London : Phaidon Press Limited, 1998)
Ader, Bas Jan ; Arnatt, Keith ; Art & Language ; Asher, Michael ; Atkinson, Terry ; Baldessari, John ; Barry, Robert ; Baumgarten, Lothar ; Beuys, Joseph ; Bochner, Mel ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Byars, James Lee ; Cage, John ; Dibbets, Jan ; Duchamp, Marcel ; Gonzalez-Torres, Felix ; Graham, Dan ; Haacke, Hans ; Hiller, Susan ; Hilliard, John ; Holzer, Jeny ; Horn, Roni ; Huebler, Douglas ; Kabakov, Ilya ; Kawara, On ; Klein, Yves ; Knizak, Milan ; Kosuth, Joseph ; Kounellis, Jannis ; LeWitt, Sol ; Long, Richard ; Man Ray ; Manzoni, Piero ; Mendieta, Ana ; Messager, Annette ; Morris, Robert ; Mouraud, Tania ; Nauman, Bruce ; Oiticica, Hélio ; Paolini, Giulio ; Picabia, Francis ; Piper, Adrian ; Rauschenberg, Robert ; Reinhardt, Ad ; Ruthenbeck, Reiner ; Smithson, Robert ; Toroni, Niele ; Trockel, Rosemarie ; Wall, Jeff ; Warhol, Andy ; Weiner, Lawrence ; Wilke, Hannah ; Zappa, Frank
Biografie
Engels
boek